Pentingnya Pengembangan Buku Ajar Statistika Berbasis Praktik Penyelesaian Masalah dalam Penelitian Pendidikan - Anita Anggraini; Johan Syahbrudin (Jurnal Ilmiah Wahana Pendidikan, 2021)
One of the common problems experienced by students of the Teaching and Education Faculty is that in addition to difficulties in processing, analyzing, and interpreting research data, they also do not understand what statistics to use when facing a case or problem regarding various research designs and methods. This is because there are not many case-based reference books (real problems) with practical learning approaches to solve these problems. This study aims to determine the importance of the development of statistics textbooks in educational research and the specifications of appropriate textbooks to be developed. This study uses a systematic review method with a meta-ethnographic approach to determine the required new textbook specifications. And the data from the review results were analyzed using qualitative descriptive techniques. The results show that there is a need for a statistical textbook in the field of education with practical problem solving guidelines containing Higher Order Thinking Skills (HOTS) in selecting appropriate statistical tests for various types of research designs, data processing and interpretation. The development of this textbook is also beneficial for an educator in managing learning and increasing their competence.